Experience and prospects of studying of a intoxication syndrome in an infectious pathology - S. G. Pak; O. F. Belaya; V. A. Malov; E. V. Voltchkova; A. A. Erovitchenkov (Журнал инфектологии, 2014)
On the basis of unity of initiation mechanisms of pathological changes in the organism is presented a system view at development of intoxication syndrome as an influence of key pathogenic factors of agents and as a complex cascade of pathophysiological, biochemical, structural, functional and others reactions of biological system.